KAJIAN ETNOZOOLOGI MASYARAKAT DAYAK SEBERUANG DI DESA GURUNG MALI KECAMATAN TEMPUNAK KABUPATEN SINTANG - Dewin, Veneranda Lusiana; Anwari, Sofwan; Prayogo, Hari (Universitas Tanjungpura, 2017)
The knowledge gained from experience is very valuable and cannot be retrieved instantly. Dayak Seberuang Sub Tempunak Regency Sintang have knowledge utilization of wildlifeÂ has been done based on experiences such as the utilization of animals for medicinal, mystical, and ritualistic consumption of art, value, sign and other so on. This knowledge must be documented considering the height of the opening activity of the community land will affect the animal population the area and it is feared will eliminate the knowledge society will be the utilization of wildlife. This research aims to record the type of animal, type of utilization of animal parts are utilized, as well as processing and usage on any kind of animals used by people in the village of Gurung Mali Tempunak Subdistrict Regency Sintang. The methods used in this research a survey method with interview techniques the taking of respondents with snowball sampling. Data retrieval or information made directly by research person selected respondents. The respondents obtained as many as 12 people. Based on the results of the interviews obtained 37 species of 32 the Dayak community exploited by Seberuang Gurung village of Mali. The family's average per family consists of only one species, except for the family, aciptridae, cervidae, felidae, Ungulates, each found 2 species. Unless species phasianidae 3 species. Utilization varied ranging from utilization of consumption, treatment, ritual, mystical, sign, and artistic value. Most utilization as the needs of consumption that is 43%. Parts of animals that utilized covers the entire body, flesh, bile, horns, feathers, skin, spines, scales, and. The meat is widely used that is 33%. The utilization of animals for drug processing more boiled and burned. The hunting technique performed tribal Power Gurung Mali still using simple tools, namely guns and snares.Key word: Dayak Seberuang, etnozoology, utilization, wildlife